1994
DOI: 10.1152/ajpheart.1994.267.1.h155
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronically elevated pulmonary arterial pressure and flow on right ventricular afterload

Abstract: The effects of pulsatile hemodynamics on right ventricle-pulmonary circulation interactions were studied in control lambs and in two lamb models of altered pulmonary hemodynamics induced at infancy: elevated pulmonary arterial pressure (PAP) was created by the infusion of monocrotaline pyrrole (MCTP), and elevated pulmonary arterial blood flow was obtained by the creation of an arteriovenous fistula (Shunt). High-fidelity PAP, midvessel Doppler blood velocity (PAV), and cardiac output (CO) were measured in ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 0 publications
3
35
0
Order By: Relevance
“…The absence of change suggests a balance between some Z c decrease due to proximal vessels distension and some Z c increase due to proximal vessel stiffness. Chronic pulmonary hypertension, when associated with higher pressure values, is generally associated with an increased Z c due to increased elastance and with increased wave reflection, due to arterial remodeling (11,14,20). Many previous studies reported RV hypertrophy in response to pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of change suggests a balance between some Z c decrease due to proximal vessels distension and some Z c increase due to proximal vessel stiffness. Chronic pulmonary hypertension, when associated with higher pressure values, is generally associated with an increased Z c due to increased elastance and with increased wave reflection, due to arterial remodeling (11,14,20). Many previous studies reported RV hypertrophy in response to pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…From impedance, spectra were derived from the 0-Hz impedance modulus or total resistance (Z 0), and the characteristic impedance (Z c) was computed as the average of moduli between 2 and 15 Hz (4). The pressure wave was separated into forward and backward components, and wave reflection was quantified as the amplitude of the reflected pressure wave (Ampl) (14,21,37). Figure 2 summarizes how RV-arterial coupling was analyzed from RV pressure-volume curves using a single-beat method (5).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, pressure waveform analysis performed in the time domain makes it possible to calculate the timing and extent of wave reflection in systemic and pulmonary circulation with measures such as augmentation index (as shown in Figure 3D), which roughly represents reflected wave summation (⌬P) in the pulmonary circuit and normalizes for the PA pulse pressure. [32][33][34][35][36][37][38][39][40] These values can be obtained easily at the time of right heart catheterization, and future studies will compare both analyses as potential prognostic indicators in patients with pulmonary hypertension and correlate with the previously described concept of capacitance. 41 …”
Section: Time-domain Analysis Of Pa Pressure Waveformsmentioning
confidence: 99%
“…This can be assessed in much the same way as the LV with E/A and EЈ/AЈ analysis. 35,83 Moreover, diastolic forward flow in the RV outflow tract may serve as a marker of RV diastolic function. [83][84][85] More recently, the improvement of PAH therapy on RV diastolic function has been noted.…”
Section: Champion Et Al Approach To the Rv-pulmonary Circulation Unitmentioning
confidence: 99%
“…Right ventricular adaptation is an important prognostic factor in acute [4] and chronic [5] pulmonary hypertension (PH). Regarding the right ventricular mechanical properties or adaptive response to PH, it is important to consider not only PH duration and severity, but also the arterial wall smooth muscle bulk and tone (active versus passive PH) [6][7][8].…”
Section: Introductionmentioning
confidence: 99%